The Analysis of Offenses in Inland Navigation in Poland 2013-2017 - Emilia Skupien (TransNav: International Journal on Marine Navigation and Safety of Sea Transportation, 2019)
The article presents an analysis of offenses in inland navigation in 2013-2017, based on the number and reasons for issuing fines by Offices of Inland Navigation in Poland. In the investigated period, in Poland, over 1,300 fines were issued on the basis of five articles of the Act of 21st of December 2000 on Inland Navigation. Based on the collected data, the most common reasons for punishing crews of inland vessels were determined and the impact of these offenses on the safety of inland navigation in Poland was identified. In addition, recommendations for changes in the classification of offenses were presented due to the too wide spectrum of individual articles, which adversely affects the ability to interpret the most common offenses and makes it difficult to assess the causes and effects of their occurrence.